Racismo, eugenia no pensamento conservador brasileiro: a proposta de povo em Renato Kehl - Góes, Weber Lopes [UNESP] (2015)
This work aims to present the social determinations regarding the objectification of the eugenics movement in Brazil from the path of Renato Kehl (1889-1974), leading exponent of eugenic ideology in Brazil. Medical and pharmaceutical, stiffer way, defended the dissemination and implementation of the eugenics project, holding conferences in Brazil and in several Latin American countries. Renato Kehl Brazilian intellectual elite would establish responsibility eugenics parameters, the success of eugenics depended on its implementation as public policy. For this purpose Renato Kehl founded in 1918, the Eugenics Society of São Paulo, with the mission to spread the eugenic idea in Brazil and implement eugenics - oriented proposals. Renato Kehl was still one of the main organizers of the movement in the creation and development institutions at the national level; in 1929, founded the Eugenics Bulletin in order to publish texts on eugenic theme in the national and international levels, as well as disclose the proposed laws based on eugenics and implemented in countries like the United States and Germany. Renato Kehl was the forerunner of the eugenics movement in Brazil and claimed that the Brazilian people would be perfectly effected if there were the extinction of feebleminded, insane, psychopaths, criminals, delinquents and diverted; epileptics, alcoholics and addicted to illicit drugs; patients (tuberculosis, leprosy and others); blind and deaf; shapeless, people dependent on welfare, the homeless, bums and destitute.